Social determinants of child health and wellbeing - Li, Jianghong; Mattes, E.; Stanley, F.; McMurray, A.; Hertzman, C. (The Australian Sociological Association, 2009)
This Editorial provides a critical review of the progress in social determinants of health research over the last two decades, suggesting new perspectives which may further our understanding of persistent social inequalities in health. It highlights the global significance of the Special Issue setting it in the context of the recently released WHO Commission on Social Determinants of Health Final Report (CSDH 2008).The Editorial introduces individual papers in the Special Issue and discusses how they are in line with, complement or provide feedback to, the WHO CSDH Final Report and its call for actions to close the health gap in a generation. Finally, based on the articles in this Special Issue and emerging themes of the global research and policy literature, it outlines a number of significant directions for future research and actions, from both methodological and theoretical points of view.